Workers with Disabilities Personal Growth Initiative: The Contribution of Family Functioning and Work Empowerment - Aprilia, Nugraini; Dhini Rama Dhania; Iranita Hervi Mahardayani; Ruth Natalia Susanti; Ruby, Arcivid Chorynia (Journal of Educational, Health and Community Psychology, 2025)
The study analyzed the relationship between family functioning and work empowerment on personal growth initiative among workers with disabilities. It involved 244 participants selected through purposive sampling, focusing on active workers across various sectors. The researchers utilized Likert scales to measure family functioning, work empowerment, and personal growth initiative, ensuring reliability with Cronbach's Alpha (α > 0.8). Normality and linearity assumptions were met before analysis. Multiple regression analysis results showed a significant relationship (F = 32.521, p < 0.01), indicating that family functioning and work empowerment explained 21.3% of the variation in personal growth initiative (R² = 0.213). These findings highlighted the importance of family support and workplace empowerment in promoting personal growth for workers with disabilities, suggesting a need for inclusive policies and support programs to enhance their quality of life.